Young people's awareness of the timing and placement of gambling advertising on traditional and social media platforms: a study of 11-16-year-olds in Australia - Samantha L. Thomas; Amy Bestman; Hannah Pitt; Rebecca Cassidy; Simone McCarthy; Christian Nyemcsok; Sean Cowlishaw; Mike Daube (BMC, 2018)
Abstract Background Research has demonstrated that the promotion of gambling, particularly within sport, may have a significant impact on positively shaping young people's attitudes towards gambling. While some governments have implemented restrictions to limit young people's exposure to gambling advertising, few studies have investigated where young people recall seeing gambling advertising, and whether they perceive that advertising restrictions have gone far enough in reducing exposure to these promotions. Method Mixed methods, interviewer-assisted surveys were conducted with n = 111 young people aged 11-16 years, who were self-reported fans of basketball in Victoria, Australia. Interviews were conducted at basketball stadiums between May and July 2018. The study assessed media viewing patterns; recall and awareness of the timing, placement, and content of gambling advertising; the impact of gambling advertising restrictions; and attitudes towards sporting organisations' roles in the promotion of gambling. Results The majority of young people recalled seeing gambling advertising on television (n = 101, 91.0%), with most recalling advertising within sporting matches or games (n = 79, 71.2%). Most young people recalled seeing gambling advertising in the early evening before 8:30 pm (n = 75, 67.6%). Just over half of young people described seeing gambling advertisements on social media (n = 61, 55.0%), and over a third (n = 40, 36.0%) recalled gambling advertising on YouTube, predominantly before watching sporting or gaming videos. The majority stated that they continued to watch sport after 8:30 pm (n = 93, 83.7%), which is when restrictions on advertising in live sport in Australia end. The majority (n = 88, 79.3%) stated that there were too many gambling advertisements in sport. Three quarters believed that sporting codes should do more to prevent young people from being exposed to advertising for gambling in sport (n = 84, 75.7%). Conclusions There is now a clear body evidence that current regulatory systems for gambling advertising are ineffective, with further restrictions urgently needed across a range of media channels to prevent exposure to promotions that may encourage young people's interest and involvement in gambling.